Hubungan Tingkat Pengetahuan dan Perilaku Masyarakat tentang Swamedikasi Batuk di Apotek Gracia Mengwi Badung - Luh Anggi Distya Pratiwi; A.A Made Krisna Dewi; Asriyanti Kristina Modena; Rosalia Tahan Bau (Lembaga Pengembangan Kinerja Dosen, 2026)
Cough self-medication was a common practice among the community because it was perceived as quick and practical; however, it posed a risk of irrational drug use when not supported by adequate knowledge. The phenomenon of many customers at Gracia Pharmacy Mengwi Badung purchasing cough medicines without consulting a pharmacist prompted the need for research on the relationship between knowledge level and self-medication behavior. This study aimed to analyze the relationship between the level of knowledge and cough self-medication behavior at Gracia Pharmacy Mengwi Badung. The study used a quantitative descriptive method with a cross-sectional approach. The research population consisted of all customers who purchased cough medicine without a doctor’s prescription, with a total sample of 30 respondents meeting the inclusion criteria through purposive sampling. The research instrument used a questionnaire. Data were collected through direct interviews and observations. Data analysis was conducted using quantitative descriptive techniques. The results showed that most respondents had a good level of knowledge (60%) and demonstrated good self-medication behavior (56.7%). Statistical analysis revealed a positive and significant relationship between knowledge level and self-medication behavior for cough (r = 0.612; p = 0.004).